Use of spike moisture content to define physiological maturity and quantify progress through grain development in wheat and barley - Celestina, Corinne; Bloomfield, Maxwell T; Stefanova, Katia; Hunt, James R (2021)
A single measurement is useful for determining how far a crop has progressed through grain development, and whether it has reached physiological maturity. Grain development is commonly assessed by using subjective, qualitative methods that describe the look and feel of the kernel or the colour of the straw. Physiological maturity in cereal crops can be determined more accurately by the grain moisture content; however, the moisture content of whole spikes is potentially quicker and easier to assess than that of individual kernels, and with a greater degree of accuracy. This experiment aimed to characterise the moisture dynamics of whole intact wheat (Triticum aestivum L.) and barley (Hordeum vulgare L.) spikes during the grain development phase and identify the spike moisture content corresponding to physiological maturity for both species. The dry matter and water contents of whole spikes of five wheat and five barley cultivars sown over six dates were determined at weekly intervals throughout the period of grain development from anthesis to harvest ripeness. Use of regression analysis determined that the spike moisture content at physiological maturity was 43% (95% confidence interval 41–45%) for wheat and 50% (95% confidence interval 49–51%) for barley, irrespective of differences in cultivar morphology, phenology and growing conditions. We demonstrate that progression through kernel development in wheat and barley can be assessed objectively and quantitatively by using spike moisture content, and we provide guidelines for accurate determination of the grain development stage using spike moisture.